2004
DOI: 10.1021/ma030465k
|View full text |Cite
|
Sign up to set email alerts
|

13C and 1H Resonance Assignment of Mercerized Cellulose II by Two-Dimensional MAS NMR Spectroscopies

Abstract: Through-bond 13C−13C and 13C−H correlations in the crystal structure of cellulose II were determined by the two-dimensional (2D) refocused INADEQUATE and MAS-J-HMQC spectra of the mercerized cellulose, which was biosynthesized by Acetobacter xylinum ATCC 10245 from the uniformly labeled glucose (d-(U-13C6)glucose). Mercerization of the bacterial cellulose was achieved in a solution of 20% NaOH in water for 2 weeks. In the 2D INADEQUATE spectrum of cellulose II, two sets of the through-bond 13C−13C connectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Thus it has been suggested that the presence of a double resonance line for C4 in spectra recorded from cellulose II (88.7 and 87.4 ppm) is related to a slight difference in the glycosidic conformations of the crystallographically distinct center and origin chains (Kono et al 2004). As already noted, the conformation of EDA-cellulose I is similar to that of the center chain of cellulose II.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…Thus it has been suggested that the presence of a double resonance line for C4 in spectra recorded from cellulose II (88.7 and 87.4 ppm) is related to a slight difference in the glycosidic conformations of the crystallographically distinct center and origin chains (Kono et al 2004). As already noted, the conformation of EDA-cellulose I is similar to that of the center chain of cellulose II.…”
Section: Resultsmentioning
confidence: 71%
“…In EDA-cellulose I the C4 resonance line is found at 84.6 ppm, whereas in spectra recorded from the native cellulose allomorphs it is found in the 89-90 ppm region, with the exception of a resonance line at 84.5 ppm that has been associated with chains at the surface of crystalline regions (Montanari et al 2005). For other cellulose allomorphs with hydroxymethyl groups in the gt conformation, there is an up field displacement of the C4 resonance line of similar size for Na-cellulose I (85.3 ppm; Porro et al 2007), but smaller or negligible displacements for Cellulose III I (87.8 ppm; Table 1) and cellulose II (88.7 and 87.4 ppm; Kono et al 2004;Dudley et al 1983). Therefore, there would appear to be little overall correlation between a change in hydroxymethyl group conformation from tg to gt and an up field shift in the C4 resonance line.…”
Section: Resultsmentioning
confidence: 97%
“…2 shows the solid-state 13 C NMR spectra of Na-cellulose IV and cellulose II samples. These are typical of Na-cellulose IV and cellulose II with the doublets from the C1, C4, and C6 signals (Kono, Numata, Erata, & Takai, 2004;Porro et al, 2007). Comparing both spectra, the peak positions of each carbon atom are almost the same, indicating a high degree of similarity in the molecular conformations of their cellulose chains.…”
Section: Synchrotron X-ray Fiber Diffractionmentioning
confidence: 83%
“…MAS-J-HMQC, [166] MAS-J-HSQC [167] and refocused INEPT [168] enable the high-resolution determination of the 1 H chemical shifts of hydrogen atoms directly bonded to carbons, with applications at natural abundance in 13 C including a tripeptide, [169] celluloses, [157,158] maltose anomers [52] and a penicillin G K þ salt. [170] As an example, Figure 11b presents a 13 C-1 H MAS-J-HMQC (recorded in 34 h experimental time at 7.0 T) spectrum of tunicate cellulose at natural abundance.…”
Section: Identification Of Through-bond Connectivitiesmentioning
confidence: 99%